SIRT1 Is Involved in the Neuroprotection of Pterostilbene Against Amyloid β 25–35-Induced Cognitive Deficits in Mice - Zhu, Lin; Lu, Fangjin; Zhang, Xiaoran; Liu, Siyuan; Mu, Ping (Frontiers in Pharmacology, 2022)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by amyloid-β (Aβ) deposits and neurofibrillary tangles. Pterostilbene (PTE), a bioactive component mainly in blueberries is found to have neuroprotective properties. However, the specific underlying mechanisms of PTE in protecting AD remain unclear. Herein, we explored its effects on Aβ25–35-induced neuronal damage in vivo and in vitro and further compared the roles with its structural analog resveratrol (RES) in improving learning-memory deficits. We found that intragastric administration of PTE (40 mg/kg) displayed more effective neuroprotection on Aβ25–35-induced cognitive dysfunction assessed using the novel object test, Y-maze test and Morris water maze test. Then, we found that PTE improved neuronal plasticity and alleviated neuronal loss both in vivo and in vitro. Additionally, PTE upregulated the expression of sirtuin-1 (SIRT1), nuclear factor erythroid 2-related factor 2 (Nrf2) and the level of superoxide dismutase (SOD), and inhibited mitochondria-dependent apoptosis in Aβ25–35-treated group. However, SIRT1 inhibitor EX527 reversed the neuroprotection and induced a drop in mitochondrial membrane potential in PTE-treated primary cortical neurons. Our data suggest that PTE enhancing learning-memory ability and improving neuroplasticity might be related to inhibiting mitochondria-dependent apoptosis via antioxidant effect regulated by SIRT1/Nrf2 in AD.